Windows of opportunity: Ocean warming shapes temperature‐sensitive epigenetic reprogramming and gene expression across gametogenesis and embryogenesis in marine stickleback - Alexandre Fellous; K. Mathias Wegner; Uwe John; Felix C. Mark; Lisa N. S. Shama (Global Change Biology, 2022)
Rapid climate change is placing many marine species at risk of local extinction. Recent studies show that epigenetic mechanisms (e.g. DNA methylation, histone modifications) can facilitate both within and transgenerational plasticity to cope with changing environments. However, epigenetic reprogramming (erasure and re‐establishment of epigenetic marks) during gamete and early embryo development may hinder transgenerational epigenetic inheritance. Most of our knowledge about reprogramming stems from mammals and model organisms, whereas the prevalence and extent of reprogramming among non‐model species from wild populations is rarely investigated. Moreover, whether reprogramming dynamics are sensitive to changing environmental conditions is not well known, representing a key knowledge gap in the pursuit to identify mechanisms underlying links between parental exposure to changing climate patterns and environmentally adapted offspring phenotypes. Here, we investigated epigenetic reprogramming (DNA methylation/hydroxymethylation) and gene expression across gametogenesis and embryogenesis of marine stickleback ( Gasterosteus aculeatus ) under three ocean warming scenarios (ambient, +1.5 and +4°C). We found that parental acclimation to ocean warming led to dynamic and temperature‐sensitive reprogramming throughout offspring development. Both global methylation/hydroxymethylation and expression of genes involved in epigenetic modifications were strongly and differentially affected by the increased warming scenarios. Comparing transcriptomic profiles from gonads, mature gametes and early embryonic stages showed sex‐specific accumulation and temperature sensitivity of several epigenetic actors. DNA methyltransferase induction was primarily maternally inherited (suggesting maternal control of remethylation), whereas induction of several histone‐modifying enzymes was shaped by both parents. Importantly, massive, temperature‐specific changes to the epigenetic landscape occurred in blastula, a critical stage for successful embryo development, which could, thus, translate to substantial consequences for offspring phenotype resilience in warming environments. In summary, our study identified key stages during gamete and embryo development with temperature‐sensitive reprogramming and epigenetic gene regulation, reflecting potential ‘windows of opportunity’ for adaptive epigenetic responses under future climate change.

Genome Survey of Chromatin-Modifying Enzymes in Threespine Stickleback: A Crucial Epigenetic Toolkit for Adaptation? - Alexandre Fellous; Lisa N. S. Shama (Frontiers in Marine Science, 2019)

Modulatory effect of the exudates released by the brown kelp Lessonia spicata on the toxicity of copper in early developmental stages of ecologically related organisms - Alexandre Fellous; Santiago Andrade; Francisco Vidal-Ramirez; Ricardo Calderón; Jessica Beltran; Juan A. Correa (Environmental Science and Pollution Research, 2017)

DNA Methylation Is Crucial for the Early Development in the Oyster C. gigas - Guillaume Riviere; Guan-Chung Wu; Alexandre Fellous; Didier Goux; Pascal Sourdaine; Pascal Favrel (Marine Biotechnology, 2013)